Pengaruh Motivasi, Strategi, Budaya, Harga dan Fitur Produk Terhadap Keputusan Pembelian Mobil Datsun: (Studi Empiris pada Konsumen Mobil Datsun di Indomobil Nissan Purwokerto) - Tri Hutomo; Pujiharto; Eko Haryanto; Azmi Fitriati (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to examine the effect of motivation, strategy, consumer culture, price and product features on the decision to purchase a Datsun brand car in Indomobil Nissan Purwokerto and the Banyumas Regency area. The method used is a survey by purposive sampling. The number of respondents as many as 60 people, namely Datsun car users. The data were tested statistically. The components tested are validity test, reliability test. The test consists of classical assumptions, multiple linear analysis, coefficient of determination, and hypothesis testing. The results show that consumer motivation, strategy, culture, price, product features have a significant effect on purchasing decisions. This means that the type of product, perception, culture, price and features are taken into consideration by consumers in making purchasing decisions on Datsun brand cars in Indomobil Nissan Purwokerto and the Banyumas Regency area. This condition is supported by the results of the SWOT analysis which shows a positive value